A Computational Study on the Performance of Earth Air Heat Exchanger (EAHE) Using Different Duct Geometries and Material Combinations - Singh, Charnveer; Kocher, Gautam; Singh, Pardeep (International Journal of Computer Sciences and Engineering, 2025)
The study explores the thermal performance of Earth air Heat Exchanger (EAHE) for warming and cooling modes under Indian climatic conditions. A 3-dimensional, computational fluid dynamics (CFD) model is produced in ANSYS FLUENT v15.0 under relentless conditions for various pipe materials and pipe geometries. The pipe geometries considered for the investigation are round; square; triangular and circular-corrugated and the pipe materials considered are Aluminium and Steel. This paper expects to locate the optimal geometry and pipe material to acquire ideal temperature variation for thermal comfort. The effect of ambient temperature, mass stream rate, Reynolds Number, Prandtl number and Nussult number were considered. Results demonstrated that if the length of the pipe increases, the temperature at the outlet diminishes in cooling mode and vice versa. The greatest temperature drop watched is 12.05K and 16.65K during cooling and warming mode respectively for the triangular-corrugated pipe. Moreover, most extreme temperature variation was watched for aluminium pipe material at 2m/s. It can be presumed that corrugated aluminium pipes can be utilized to get ideal temperature drop for better thermal comfort. In addition, as the mass stream rate increases, the temperature variation also increases regardless of the pipe materials and pipe cross-segments